Coronavirus disease 2019 (COVID-19) or preeclampsia: pathomorphological differential diagnosis of placental changes - T.V. Savchuk; I.V. Leshchenko (Medičnì Perspektivi, 2025)
Coronavirus disease 2019 (COVID-19) and preeclampsia (PE) have shared clinical and pathological manifestations, creating a diagnostic challenge. The aim of the study was to identify pathomorphological changes in the placenta that are diagnostically significant for COVID-19 and preeclampsia. We studied the placenta in full-term pregnancies with maternal COVID-19 (Group I, n=80; Subgroup I.1 – COVID-19 at 19–34 weeks of gestation, n=48; Subgroup I.2 – COVID-19 at 35–40 weeks, n=32), the placenta in cases of preeclampsia (PE, n=30) – Group II (Subgroup II.1 – with mild PE; Subgroup II.2 – with moderate and severe PE), and the placenta in the comparison group, n=40. Macroscopic, microscopic, immunohistochemical, morphometric, and statistical methods were used. Placentae in the main groups were characterized by circulatory disorders. Placentitis was present exclusively in Group I. Arteriolosclerosis with vascular lumen obliteration was predominantly detected in Group II and was associated with arteriolar wall hyalinosis: Subgroup II.1 – 75% (95% CI: 49.5%–93.5%), Subgroup II.2 – 100% (95% CI: 87.3%–100%) compared to 25% (95% CI: 13.6%–38.4%) in Subgroup I.1, where it was caused by the proliferation of smooth muscle cells in the arteriolar wall followed by fibrosis, and was not observed in Subgroup I.2. A reduction in the number of terminal chorionic villi was observed in Subgroup I.1 and Subgroup II.2: 16.6 [10; 25] and 12.8 [12; 14], respectively. This was attributed to delayed villous maturation caused by vascular damage in the stem villi. The placenta in Subgroup I.2 was characterized by stromal edema of terminal villi, which led to external compression of the vessels, resulting in a reduced percentage of vessels within the villi – 26.9% [20.9%; 35.6%]. The reduction in vessel percentage in Group II.2 – 29.0% [25.6%; 34.2%] was associated with fibrosis of the chorionic villous stroma. These indicators significantly differed (p<0.0001) from Group I.1 and II.1: 45.2% [40.9%; 48.3%] and 57.6% [50.2%; 64.1%], respectively, and from the comparison group: 67.8% [58.78%; 73.7%]. Compensatory changes, such as an increase in syncytial knots, were observed in Subgroup I.2 and Subgroup II.1, with densities of 12.8 [11; 14] and 9.1 [8; 10], respectively, compared to 5.7 [5; 7] in the comparison group. A reduction in the percentage of the intervillous space was observed in Subgroup I.2 and Subgroup II.1: 26.0% [20.7%; 33.8%] and 29.2% [18.9%; 42.2%], respectively, versus 44.9% [40.5%; 49.6%] in the comparison group; p<0.0001. Placentitis is the main pathomorphological difference in placental changes in COVID-19 compared to preeclampsia. Pathomorphological changes in the placenta during the acute phase of COVID-19 and in mild preeclampsia, despite differences in disease pathogenesis, shared common features: microcirculatory disturbances and an increased number of syncytial knots as a compensatory response to reduced intervillous space (caused by villous stromal edema in COVID-19 and angiomatous changes in terminal villi in preeclampsia). Placental changes in moderate and severe preeclampsia, characterized by infarctions, arteriolosclerosis, and delayed villous maturation (distal villous hypoplasia), were similar to changes observed in COVID-19 in the second trimester of pregnancy.